Study The Severe Effects of Iron Compounds Presenting in Sandstone on the Deterioration of Wall Paintings of Archaeological Tombs in Bahariya Oasis - Egypt - Kader, Rabea Radi Abdel; El–Sayed, Shaimaa Sayed Mohamed; Abo-El Yamin, Ahmed (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
The Wall paintings in Bahariya oasis expose to various deterioration factors, especially the resulted deterioration from the geological nature of sandstones' supports; sandstone of Bahariya formation is considered the weakest sandstone type in Egypt because of its geological formation which contains a very big percentage of iron oxides. Sandstone samples were taken, analyzed and examined by x-ray diffraction and scanning electron microscope, the iron oxides are thecement material in sandstone which affect negatively on the wall paintings in the selected tombs (Badi –Ishtarand Bannantiu tombs),they caused a lot of deterioration phenomena to the wall painting layers like: layers loss,black spots, cracking through all the layers and sandstone support weakness that threatens the remaining wall paintings and the safety of the tombs. Iron oxides percentage in Badi – Ishtartomb is more than Bannantiu tomb and this is reflected on the wall paintings case in Badi – Eshtar. This research sheds the light on this phenomenon and its effect on the wall painting's deterioration.